2018
DOI: 10.1021/acs.joc.8b01892
|View full text |Cite
|
Sign up to set email alerts
|

DBU-Promoted Dynamic Kinetic Resolution in Rh-Catalyzed Asymmetric Transfer Hydrogenation of 5-Alkyl Cyclic Sulfamidate Imines: Stereoselective Synthesis of Functionalized 1,2-Amino Alcohols

Abstract: Dynamic kinetic resolution (DKR)-driven asymmetric transfer hydrogenation of 5-alkyl cyclic sulfamidate imine produces the corresponding sulfamidate with excellent levels of diastereo- and enantioselectivity by employing a HCOH/DBU mixture as the hydrogen source in the presence of the Noyori-type chiral Rh-catalyst at room temperature for 1 h. In this process, DKR was induced by DBU-promoted rapid racemization of the substrate. Stereoselective transformations of the resulting cyclic sulfamidates to functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…For example, ring-opening reactions of chiral cyclic sulfamidates can offer convenient and efficient access to chiral amines, amino alcohols, amino acids, and their derivatives (Boulton et al., 1999, Wei and Lubell, 2000, Espino et al., 2001, Cohen and Halcomb, 2001, Cohen and Halcomb, 2002, Atfani et al., 2001, Nicolaou et al., 2002, Meléndez and Lubell, 2003, Ni et al., 2007, Rönnholm et al., 2007, Baig et al., 2010, Baig et al., 2011, Venkateswarlu et al., 2014, Albu et al., 2016, Su et al., 2016, Chen et al., 2014, Kong et al., 2015, Liu et al., 2017, Wu et al., 2018). So far the asymmetric catalytic synthetic methods of chiral cyclic sulfamidates were mainly focused on transition metal-catalyzed asymmetric intramolecular amidation of sulfamate esters (Liang et al., 2002, Liang et al., 2004, Fruit and Mueller, 2004, Zhang et al., 2005, Zalatan and Du Bois, 2008, Lin et al., 2008, Ichinose et al., 2011), additions of organoboron reagents to cyclic imines (Chen et al., 2014, Chen et al., 2018, Kong et al., 2015, Liu et al., 2017, Wu et al., 2018, Nishimura et al., 2012, Nishimura et al., 2013, Luo et al., 2012a, Luo et al., 2012b, Wang et al., 2013, Hepburn et al., 2013, Wang and Xu, 2013, Zhang et al., 2016a), and asymmetric reduction of cyclic ketimines (Wang et al., 2008, Yu et al., 2009, Kang et al., 2010, Lee et al., 2011, Lee et al., 2012, Han et al., 2011, Liu et al., 2019, Itsuno et al., 2014, Seo et al., 2015, Kim et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ring-opening reactions of chiral cyclic sulfamidates can offer convenient and efficient access to chiral amines, amino alcohols, amino acids, and their derivatives (Boulton et al., 1999, Wei and Lubell, 2000, Espino et al., 2001, Cohen and Halcomb, 2001, Cohen and Halcomb, 2002, Atfani et al., 2001, Nicolaou et al., 2002, Meléndez and Lubell, 2003, Ni et al., 2007, Rönnholm et al., 2007, Baig et al., 2010, Baig et al., 2011, Venkateswarlu et al., 2014, Albu et al., 2016, Su et al., 2016, Chen et al., 2014, Kong et al., 2015, Liu et al., 2017, Wu et al., 2018). So far the asymmetric catalytic synthetic methods of chiral cyclic sulfamidates were mainly focused on transition metal-catalyzed asymmetric intramolecular amidation of sulfamate esters (Liang et al., 2002, Liang et al., 2004, Fruit and Mueller, 2004, Zhang et al., 2005, Zalatan and Du Bois, 2008, Lin et al., 2008, Ichinose et al., 2011), additions of organoboron reagents to cyclic imines (Chen et al., 2014, Chen et al., 2018, Kong et al., 2015, Liu et al., 2017, Wu et al., 2018, Nishimura et al., 2012, Nishimura et al., 2013, Luo et al., 2012a, Luo et al., 2012b, Wang et al., 2013, Hepburn et al., 2013, Wang and Xu, 2013, Zhang et al., 2016a), and asymmetric reduction of cyclic ketimines (Wang et al., 2008, Yu et al., 2009, Kang et al., 2010, Lee et al., 2011, Lee et al., 2012, Han et al., 2011, Liu et al., 2019, Itsuno et al., 2014, Seo et al., 2015, Kim et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This DBU promoted protocol utilises a Noyori-type chiral rhodium catalyst and HCOOH/ DBU as a hydrogen source. 57 This particular process takes place through DBU promoted rapid racemisation of the cyclic imine substrates. Through this methodology a wide range of sulfamidates have been prepared in excellent diastereo-and enantioselectivities (Fig.…”
Section: Rhodium-catalysed Imine Athmentioning
confidence: 99%
“…In 2018, Lee and co-workers reported a convenient and highly stereoselective ATH to access cyclic sulfamidates, cis-4-aryl-5-alkyl-1,2,3-oxathiazolidine S,S-dioxides (Scheme 58). 71 Attempts to increase the stereoselectivity of ATH reactions of 5-alkyl-substituted cyclic sulfamidates showed that stronger bases than Et 3 N, such as DBU, facilitated rapid racemization of the configurationally labile cyclic imine substrates and led to better stereoselectivities. Consequently, the Rh-catalyzed ATH/DKR was conducted in combination with HCO 2 H/DBU ( Dieses Dokument wurde zum persönlichen Gebrauch heruntergeladen.…”
Section: Scheme 57mentioning
confidence: 99%